Mangrove ecosystem density mapping using Normalized Difference Vegetation Index (NDVI) Analysis in the Coastal Area of Pasekan District, Indramayu Regency - Muhamad Fatah Nashrullah; Gatot Yulianto; Mohammad Mukhlis Kamal (Universitas Malikussaleh, 2026)
The mangrove ecosystem in the coastal area of Pasekan Subdistrict, Indramayu Regency, is experiencing environmental pressure due to coastal abrasion and land-use conversion, which affect vegetation density. This study aims to analyze changes in mangrove density during 2015–2025 using the Normalized Difference Vegetation Index (NDVI) method based on Landsat 8 and Sentinel-2 imagery. The analysis included image preprocessing, NDVI calculation, density classification, and spatial change analysis. The results showed that mangrove density area decreased by 29.2293 ha (9.38%), from 311.7671 ha in 2015 to 282.5378 ha in 2025. The decline mainly occurred in the very high-density class due to coastal abrasion and land conversion into ponds and settlements. Meanwhile, the increase in low to medium-density classes indicates mangrove regeneration and rehabilitation in several locations. In addition, Sentinel-2 imagery provided better spatial detail than Landsat 8 for mangrove density identification. Keywords: Mangrove density; Landsat 8; NDVI; Sentinel